2011
DOI: 10.1134/s0022476611060175
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of N,N′-Bis-(2,5-dimethoxybenzylidene)-1,3-diaminopropane

Abstract: The Schiff-base compound N,N′-Bis-(2,5-dimethoxybenzylidene)-1,3-diaminopropan, (2,5-MeO-ba) 2 pn, is synthesized and characterized by elemental analysis, FT-IR and 1 H NMR spectroscopy. The crystal structure of (2,5-MeO-ba) 2 pn is determined by X-ray single crystal diffraction analysis. The X-ray diffraction analysis at 120 K reveals that (2,5-MeO-ba) 2 pn crystallizes in the orthorhombic system, Fdd2 space group with a = 29.339(9) Å, b = 29.4073(11) Å, c = 4.4524(2) Å, V = 3840.8(3) Å 3 , μ = 0.72 mm -1 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The methyl hydrogen atoms were allowed to rotate freely about the adjacent C-C bonds. The isotropic atomic displacement parameters of hydrogen atoms were set to 1.5U eq (C) for methyl groups and to 1. are consistent with the sp 2 hybrid character of C7 and N1 atoms [20][21][22][23][24][25]. There is one intramolecular hydrogen bond of the O-HѱN type in the compounds L 1 and L 2 ( Table 3).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The methyl hydrogen atoms were allowed to rotate freely about the adjacent C-C bonds. The isotropic atomic displacement parameters of hydrogen atoms were set to 1.5U eq (C) for methyl groups and to 1. are consistent with the sp 2 hybrid character of C7 and N1 atoms [20][21][22][23][24][25]. There is one intramolecular hydrogen bond of the O-HѱN type in the compounds L 1 and L 2 ( Table 3).…”
supporting
confidence: 72%
“…Recently, our group has reported the syntheses and crystal structures of Schiff base compounds [ 4,[20][21][22][23][24][25]. Herein, we report the synthesis and the crystal structure determination of novel bis-NOacyclic Schiff base compounds, derived from 3-methoxy-4-(2-(4-formyl-2-ethoxyphenoxy)ethoxy)benzaldehyde with 2-aminophenol (L 1 ) or 4-aminophenol (L 2 ) (Scheme 1).…”
mentioning
confidence: 99%
“…The Schiff bases are one of the most important compounds that are not only used as ligand for preparation various coordination compounds with transition metal ions such as copper(I) [1][2][3], copper(II) [4,5], Ag(I) [1], Zn(II) [6][7][8], Hg(II) [9] and V(IV) [10], but also for various application and properties such as fluorescent pH prob [11], photoluminscent [12], detection of Fand AcO - [13], corrosion inhibition [14] and optical properties [15]. This is due to the fact that, Schiff base compounds are a) easily obtained by one-step procedure [16][17][18][19] b) the existence of tautomerization between phenol-imine and keto-amine form in Schiff bases derived from salicylaldehyde derivatives having 2-hydroxy group [20,21] and c) are prepared stable complexes [1][2][3][4][5][6][7][8][9][10]. Reimann et al [22] prepare water-soluble sulfonate Schiff base ligands and reported the fluorescent detectors of various for metal ions.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%